PEMBERITAAN DAKWAH USTADZ HANAN ATTAKI SEBELUM DAN SETELAH BERGABUNG DENGAN NAHDLATUL ULAMA (NU) ANALISIS FRAMING MEDIA ONLINE DETIK.COM - Misroji; Nur Rahman Shalahudin (STAI DI AL-HIKMAH, 2025)
This study analyzes the framing of Detik.com’s news coverage on Ustadz Hanan Attaki’s preaching before and after joining Nahdlatul Ulama (NU). Using Robert N. Entman’s framing analysis method, this research highlights changes in news construction related to Ustadz Hanan Attaki’s preaching in East Java. This qualitative study employs content analysis techniques, examining the themes of the news, interviews with sources, and reported events. Data were collected from Detik.com news articles during two periods: before and after Hanan Attaki joined NU. The framing analysis includes four elements: define problems, diagnose causes, make moral judgments, and treatment recommendation.The findings show that before joining NU, Detik.com’s news coverage tended to be neutral, with some sympathy towards Hanan Attaki, receiving negative responses from some Nahdlatul Ulama figures. After joining NU, the framing of the news changed, showing increased support and acceptance from NU figures and the community.